2006
DOI: 10.1093/ietele/e89-c.12.1920
|View full text |Cite
|
Sign up to set email alerts
|

On Comparison of Constrained and Unconstrained Evolutions in Analogue Electronics on the Example of "LC" Low-Pass Filters

Abstract: SUMMARYThe Evolutionary Electronics refers to the design method of electronic circuits with the help of Evolutionary Algorithms. Over the years huge experience has been accumulated and tremendous results have been achieved in this field. Two obvious tendencies are prevailing in the area over designers to improve the performance of Evolutionary Algorithms. First of all, as with any solution-search-algorithm, the designers try to reduce the potential solution space in order to reach the optimum solution faster, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In earlier works, we already had reported about some aspects of DM and adaptation [1,3]. In later works, we found that the system performs better at SRs 10 times lower than before (from 10% to 1%) [3].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…In earlier works, we already had reported about some aspects of DM and adaptation [1,3]. In later works, we found that the system performs better at SRs 10 times lower than before (from 10% to 1%) [3].…”
Section: Introductionmentioning
confidence: 62%
“…In this work, we use relatively large populations (from 15,000 to 35,000 individuals evolving in parallel), each of which uses very low selection rates (SR) from 0.2% to 2% and aggregately the SR of the system reaches 0.048%. Furthermore, the proposed technique theoretically enables all the parallel evolutions "focus" on a single chromosome at one generation, which in our experimental case can bring up to 0.0006% SR 1 .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations